Hemodynamic Stability with Intrathecal Prilocaine 2% in Caesarean Section Patient with Ebstein’s Anomaly: A Case Report - Rifqi Taufiq Rasyid; Putu Herdit Sudiantara; Tjahya Ariyasa EM; Tjokorda Gde Agung Senapathi (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif (PERDATIN) / The Indonesian Society of Anesthesiology and Intensive Care (INSAIC), 2026)
Introduction: Ebstein’s anomaly is a rare congenital malformation of the tricuspid valve that predisposes pregnant patients to significant hemodynamic instability due to increased circulating volume, cardiac output, and catecholamine levels during pregnancy. Anesthetic management in this population requires careful maintenance of preload, afterload, and sinus rhythm to avoid worsening right-to-left shunting and arrhythmias. Case Description: A 31-year-old gravida 2 para 1 woman (G2P1001) at 37 weeks of gestation with Ebstein’s anomaly type C and severe tricuspid regurgitation who underwent cesarean section due to fetal distress. Spinal anesthesia was performed using hyperbaric prilocaine 2% (80 mg), followed by bilateral ultrasound-guided transversus abdominis plane block for postoperative analgesia. Throughout the 45-minute procedure, the patient maintained stable hemodynamics without episodes of hypotension or arrhythmias. Postoperative recovery in the Obstetric High Dependency Unit remained uneventful, with consistent vital signs and adequate pain control. A healthy neonate was delivered. Conclusion: This case demonstrates that intrathecal prilocaine 2% can provide effective surgical anesthesia while preserving hemodynamic stability in selected parturients with Ebstein’s anomaly. The pharmacological characteristics of prilocaine, rapid onset, intermediate duration, and a favorable sympathetic profile, make it a potential alternative to longer-acting agents in patients at risk of hemodynamic compromise. Further studies are needed to validate its safety and efficacy in parturients with congenital cardiac disease.